Physical Activity and the Association of Common FTO Gene Variants With Body Mass Index and Obesity - Rampersaud, Evadnie (2008)
BACKGROUND: Common FTO (fat mass and obesity associated) gene variants have recently been associated with body mass index (BMI) and obesity in several large studies. The role of lifestyle factors (such as physical activity) in those with an underlying FTO genetic predisposition is unknown. METHODS: To determine if FTO variants are associated with BMI in Old Order Amish (OOA) individuals, and to further determine whether the detrimental associations of FTO gene variants can be lessened by increased physical activity, a total of 704 healthy OOA adults were selected from the Heredity and Phenotype Intervention (HAPI) Heart Study, an investigation of gene × environment interactions in cardiovascular disease, for whom objective quantified physical activity measurements were available and for whom 92 single-nucleotide polymorphisms (SNPs) in FTO were genotyped. RESULTS: Twenty-six FTO SNPs were associated with BMI (P =.04 to <.001), including rs1477196 (P <.001) and rs1861868 (P <.001), 2 SNPs in moderate linkage disequilibrium in the OOA (D′=0.82; r(2)=0.36). Stratified analyses of rs1861868 revealed its association with BMI to be restricted entirely to those subjects with low sex-and age-adjusted physical activity scores (P <.001); in contrast, the SNP had no effect on those with above-average physical activity scores (P = .29), with the genotype × physical activity interaction achieving statistical significance (P =.01). Similar evidence for interaction was also obtained for rs1477196. CONCLUSIONS: Our results strongly suggest that the increased risk of obesity owing to genetic susceptibility by FTO variants can be blunted through physical activity. These findings emphasize the important role of physical activity in public health efforts to combat obesity, particularly in genetically susceptible individuals.